2016
DOI: 10.3389/fmicb.2016.01713
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Nisin-Polymyxin Combinations for the Control of Pseudomonas Biofilm Formation

Abstract: The emergence and dissemination of multi-drug resistant pathogens is a global concern. Moreover, even greater levels of resistance are conferred on bacteria when in the form of biofilms (i.e., complex, sessile communities of bacteria embedded in an organic polymer matrix). For decades, antimicrobial peptides have been hailed as a potential solution to the paucity of novel antibiotics, either as natural inhibitors that can be used alone or in formulations with synergistically acting antibiotics. Here, we evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 48 publications
1
61
0
1
Order By: Relevance
“…Treatment with a combination of nisin and a traditional antibiotic would theoretically reduce the incidence of resistance. Indeed, several studies have demonstrated synergistic relationships between conventional antibiotics and nisin against bacteria such as staphylococci, including methicillin‐resistant forms (Piper et al , ; Dosler and Gerceker, ; Okuda et al , ), enterococci (Tong et al , ), including vancomycin‐resistant enterococci (Brumfitt et al , ) and streptococci (Lebel et al , ), Pseudomonas (Naghmouchi et al , ; ) as well as E. coli and Klebsiella (Field et al ., ). These studies highlight the merits of employing antibiotic combination strategies to enhance the efficacy of available antibiotics, and ultimately, reduce the potential for resistance issues to arise in clinical settings.…”
Section: Discussionmentioning
confidence: 97%
“…Treatment with a combination of nisin and a traditional antibiotic would theoretically reduce the incidence of resistance. Indeed, several studies have demonstrated synergistic relationships between conventional antibiotics and nisin against bacteria such as staphylococci, including methicillin‐resistant forms (Piper et al , ; Dosler and Gerceker, ; Okuda et al , ), enterococci (Tong et al , ), including vancomycin‐resistant enterococci (Brumfitt et al , ) and streptococci (Lebel et al , ), Pseudomonas (Naghmouchi et al , ; ) as well as E. coli and Klebsiella (Field et al ., ). These studies highlight the merits of employing antibiotic combination strategies to enhance the efficacy of available antibiotics, and ultimately, reduce the potential for resistance issues to arise in clinical settings.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, the emergence of resistance to polymyxins has been reported [ 8 , 10 ]. Synergy between polymyxins and nisin and lacticin 3147, both bacteriocins from Gram-positive bacteria, against Gram-negative bacteria has been reported [ 13 , 20 , 21 ]. The synergy can be attributed to disruption of the outer membrane by polymyxin B allowing access of the bacteriocins to their target [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…With respect to nisin, to our knowledge this is the first report on the activation of biofilm synthesis by a subinhibitory concentration of this bacteriocin. Previous studies reported the inhibitory effect of nisin on the growth and biofilm formation of pathogenic bacteria, such as Listeria ( Smith et al, 2016 ), Staphylococcus ( Dosler and Mataraci, 2013 ; Okuda et al, 2013 ; Field et al, 2016a ), Streptococcus ( Tong et al, 2014 ), Enterococcus ( Taneja et al, 2015 ), Bacillus and Salmonella ( Bag and Chattopadhyay, 2017 ), Bacillus and Clostridium spores ( Egan et al, 2016 ), Pseudomonas ( Field et al, 2016b ), and Escherichia coli ( Al Atya et al, 2016 ), but none of them reported any biofilm activating effect by subinhibitory concentrations. Regarding O. oeni , a biocide effect of nisin on O. oeni cells in biofilms formed on stainless steel surfaces was already reported ( Nel et al, 2002 ).…”
Section: Resultsmentioning
confidence: 99%